Health seeking behaviour in management of erectile dysfunction among men in an urban African population - Abiola, Olajide O.; Adigun, Oluwaseyi J.; Ajamu, Olushola J.; Williams, Oyeronke T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Erectile dysfunction (ED) is consistent inability to achieve/maintain penile erection sufficiently enough for satisfactory sexual intercourse. It is a major sexual disorder causing significant distress in men with associated poor quality of life. Despite it being a common sexual disorder, many of the affected people do not seek medical care. The study sought to investigate health seeking behaviour in management of ED among urban dwelling African men. Methods: A cross-sectional descriptive survey method was adopted. The study population comprised of men drawn from an urban setting in Nigeria using a multi-stage sampling technique. Three hypotheses were formulated which were cultural beliefs, financial status and medical access/perception on quality of care will not significantly influence health seeking behaviour for management of ED. Researchers’ designed questionnaire validated by three experts drawn from the relevant fields with reliability co-efficient of 0.77 obtained through split half method by Pearson product moment correlation was used for data collection. The three postulated hypotheses were tested using Person product moment correlation. Results: All the three hypotheses were rejected at 0.05 alpha level of significance because their calculated r-values were greater than their critical values. Conclusions: It was concluded that cultural beliefs, financial status and access to medical facilities/perception of quality of care from such medical facilities influence the health seeking behaviour of men in the management of ED.